TEAM GAME TEACHING (TGT) AND INSTRUMENTED TEAM LEARNING (ITL): MEDIA FOR TEACHING ACHIEVEMENT MOTIVATION APPROACH - Canencia, Crisostomo C (Journal of Agriculture and Technology Management, 2008)
Team Game Teaching (TGT) and the Instrumented Team Learning (ITL) served as an objective teaching evaluation technique for teaching achievement motivation approach. It is driven with motivating factor which encouraged students to actively participate in the teaching-learning process for better score performance. Hence, the study showed that perception in cognitive, affective, psychomotor and language domain in the post test is too high which badly contribute to negative correlation. Means, it was highly perceived but manifested with low score. However, t-test analysis on paired mean scores from the pretest and the post test revealed a high significant difference at 1% and 5% level of significance in the improvement of post test score where achievement motivation approach is applied.